O erotismo na constituição da subjetividade em "Vozes guardadas", de Elisa Lucinda - Silva, Yago Viegas da (2023)
The poetry authored by black women in Brazil has consistently sought to transfigure the paradigm of pain that has been historically and culturally imposed upon these bodies. This poetic production, in its most diversified form, draws attention to the construction and recognition of a poetic identity that engages with various themes and meanings, all of which are highly significant and necessary for the development of a new perspective concerning both literature authored by black women and the redefinition of reality itself. When we talk about black and female-authored poetry in Brazil, it is in the contemporary era that we find an exponent poetic production, and it is within this context that Elisa Lucinda, a poet from Espírito Santo, and her anthology Vozes Guardadas (2016) can be found. This anthology is a collection of poems written by the author between 2005 and 2016, published by Editora Record. In this work, eroticism emerges as a vital resource for the constitution of subjectivity and the identity of black women (both from the perspective of the text and black female authorship), in a way that we can conceive it as a generative force that offers these subjugated and objectified female bodies the possibility of liberation, vocalization, and the construction of a politics that values the experience with the body and memory. Thus, the main objective of this research is to reflect on eroticism as a constitutive element of subjectivity in Elisa Lucinda's work. Our corpus of analysis is composed of the section "Livro do Desejo" (Book of Desire), which forms the second part of the anthology and where eroticism can be perceived as a recurring theme, whether through the valorization of bodily experience in the elaboration of meanings or through remembrance, as a way to relive pleasure through experiences stored in memory. Our research is based on the reflections of Lorde (2021), Dussel (2016), Saffioti (2019), Bataille (2021), Cuti (2010), Hooks (2010), Siscar (2016; 2010), Evaristo (2005), among others.